Peripheral blood stem cell mobilization with pegylated granulocyte colony stimulating factor in children. Issue 6 (10th July 2021) - Thakkar, Dhwanee; Tiwari, Aseem K; Pabbi, Swati; Kapoor, Rohit; Aggarwal, Geet; Rastogi, Neha; Yadav, Satya Prakash
Abstract: Background and Aim: We report here our experience of using pegylated granulocyte colony stimulating factor (peg‐GCSF) for peripheral blood stem cell (PBSC) mobilization in children. Methods and results: A total of nine children suffering from high‐risk/relapsed solid tumors were mobilized with chemotherapy and peg‐GCSF (100 microgram/kg single dose). Mean age was 7.7 years (range 2–15 years).The mean time from peg‐GCSF administration to PBSC harvest was 9.7 days. Adequate stem cells (median dose 26.9 million/kg) could be harvested in all children by a single apheresis procedure. No major adverse events observed. Conclusion: It is feasible and safe to mobilize PBSC with peg‐GCSF in children with cancer.